2016
DOI: 10.1002/mop.29719
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of bandpass filter using complementary open‐ring resonator loaded HMSIW with an electric cross‐coupling

Abstract: A novel bandpass filter (BPF) with multiple transmission zeros (TZs) and wide stopband is proposed. The filter is realised using complementary open‐ring resonators (CORRs) loaded half mode substrate integrated waveguide (HMSIW). Besides, a novel electric source‐load electric cross‐coupling configuration is introduced to generate extra attenuation poles at either side of the passband, which improves the passband selectivity and the stopband suppression level. Based on this structure, a BPF operating at 5.8 GHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The measured transmission zeros, which were observed at 4.7, 7.75, 8.6, and 9.35 GHz with return losses of 45.7, 21.9, 48.1, and 41.5 dB, respectively, generated a wide stop-band extending from 100 MHz to 3.17 GHz and 4.21 GHz to 10 GHz. Table 1 indicated that our developed BPF exhibits a noticeable advantage of higher number of transmission zeros, and therefore, better stop-band selectivity than several recently reported BPFs [17][18][19][20][21][22]. Additionally, the present BPF exhibits a more compact effective size Moreover, the superior pass-band selectivity of the proposed BPF is marked by the lower insertion loss and higher return loss.…”
Section: Multipath Coupled Bpf Analysismentioning
confidence: 69%
“…The measured transmission zeros, which were observed at 4.7, 7.75, 8.6, and 9.35 GHz with return losses of 45.7, 21.9, 48.1, and 41.5 dB, respectively, generated a wide stop-band extending from 100 MHz to 3.17 GHz and 4.21 GHz to 10 GHz. Table 1 indicated that our developed BPF exhibits a noticeable advantage of higher number of transmission zeros, and therefore, better stop-band selectivity than several recently reported BPFs [17][18][19][20][21][22]. Additionally, the present BPF exhibits a more compact effective size Moreover, the superior pass-band selectivity of the proposed BPF is marked by the lower insertion loss and higher return loss.…”
Section: Multipath Coupled Bpf Analysismentioning
confidence: 69%
“…The working principle of the proposed structures is based on the theory of evanescent‐mode propagation. According to the theory of evanescent‐mode propagation, an additional passband below the waveguide cutoff could be obtained by loading the electric scatterers on the waveguide surface . The CGRs behave as electric dipoles and are good candidates to behave as electric scatterers.…”
Section: Siw–cgr Filtermentioning
confidence: 99%
“…According to the theory of evanescent-mode propagation, an additional passband below the waveguide cutoff could be obtained by loading the electric scatterers on the waveguide surface. 12,13,21,22 The CGRs behave as electric dipoles and are good candidates to behave as electric scatterers. Therefore, according to the theory of evanescent-mode propagation, by loading the proposed CGR unit-cell on the metal cover of the SIW structure, an additional passband below the waveguide cutoff can be achieved.…”
Section: Siw-cgr Filtermentioning
confidence: 99%
“…Based on evanescent-mode propagation, a compact SIW bandpass filter using broad side coupled CSRR [22] and fractal open complementary split-ring resonators (FOCSRRs) unit-cell has been presented [23]. Complementary open-ring resonators (CORRs) loaded half mode substrate integrated waveguide (HMSIW), with many transmission zeros and wide stopband, have been proposed [24]. Novel dual mode SIW filters that can provide multiple transmission zeros have been proposed [25].…”
Section: Introductionmentioning
confidence: 99%